2021
DOI: 10.1002/cche.10490
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features and cooking behavior of pasta from pulses

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…For this reason, this study primarily aims to investigate the effects of a thermal treatment carried out on an industrial scale, and thus representative of common industrial practice, on the molecular characteristics of starch and proteins in pulses. Red lentils (Lens culinaris) have been chosen as the raw material because they are the second-most consumed pulse after chickpeas and because their use in cereal-based products is growing [15,16]. To this aim, one thermal-treated and one non-treated sample from the same commercial batch of red lentils, produced by an Italian mill as an ingredient for food production, were compared.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this study primarily aims to investigate the effects of a thermal treatment carried out on an industrial scale, and thus representative of common industrial practice, on the molecular characteristics of starch and proteins in pulses. Red lentils (Lens culinaris) have been chosen as the raw material because they are the second-most consumed pulse after chickpeas and because their use in cereal-based products is growing [15,16]. To this aim, one thermal-treated and one non-treated sample from the same commercial batch of red lentils, produced by an Italian mill as an ingredient for food production, were compared.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial pasta from red lentils exhibited a water absorption higher than 100%, cooking loss between 7.5 and 8.1 g/100 g, and firmness between 398 and 437 N [ 7 ]. Differences among the studies might be due to differences in processing conditions, including pasta shape.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the decades, structure-quality relationships have been studied in refined [ 1 ] and wholegrain [ 2 , 3 ] wheat pasta, where gluten plays a key role in assuring the typical “al dente” texture of the cooked product, as well as in gluten-free pasta [ 4 , 5 , 6 ], where starch modifications are strategic in creating a cohesive structure. On the contrary, very little information is available so far on the role of starch and protein in defining the quality of pulse pasta—the latest innovation in the pasta sector—containing about 60% of starch and 20% of proteins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of yellow lentils, extrusion-cooking process led to pasta with better texture than the traditional process since the former promoted greater starch gelatinisation and reorganisation (Bresciani et al, 2021b). In a more recent study, Bresciani et al (2022c) found that the pre-gelatinisation step modified starch and protein organisation in red lentils. However, it is still unclear how such modification would impact pasta quality.…”
Section: Introductionmentioning
confidence: 99%